An app-, web- and social support-based weight loss intervention for adults with obesity: the HelpMeDoIt! feasibility RCT - Sharon Anne Simpson; Lynsay Matthews; Juliana Pugmire; Alex McConnachie; Emma McIntosh; Elinor Coulman; Kathryn Hughes; Mark Kelson; Sarah Morgan-Trimmer; Simon Murphy; Olga Utkina-Macaskill; Laurence Moore (NIHR Journals Library, 2020)
Background: Finding solutions to rising levels of obesity continues to be a major public health focus. Social support has an important role in successful weight loss, and digital interventions can reach a large proportion of the population at low cost. Objective: To develop and assess the feasibility and acceptability of an application (app), web- and social support-based intervention in supporting adults with obesity to achieve weight loss goals. Design: Stage 1 - intervention development phase involved three focus groups (n = 10) with users, and think-aloud interviews and field testing with another group (n = 28). Stage 2 - the intervention and evaluation methods were explored in a feasibility randomised controlled trial with economic and process evaluation. Setting: Greater Glasgow and Clyde, UK. Participants: Adults with a body mass index of ≥ 30kg/m2 who owned a smartphone and were interested in losing weight were randomised 2 : 1 (intervention : control) and followed up at 12 months. Recruitment took place in April-October 2016. Interventions: The intervention group had access to HelpMeDoIt! for 12 months. This encouraged them to (1) set goals, (2) monitor progress and (3) harness social support by inviting 'helpers' from their existing social network. The control group received a healthy lifestyle leaflet. Main outcome measures: Data from stage 1 informed the intervention design. Key measures in stage 2 assessed the feasibility and acceptability of the intervention and trial methods against prespecified progression criteria. Three primary outcomes were explored: body mass index, diet and physical activity. Secondary outcomes included weight, waist and hip circumference, social support, self-efficacy, motivation, mental health, health-related quality of life, NHS resource use, participant-borne costs and intervention costs. Qualitative interviews with participants (n = 26) and helpers (n = 9) explored the feasibility and acceptability of the trial methods and intervention. Results: Stage 1 produced (1) a website that provided evidence-based information for lifestyle change and harnessing social support, and (2) an app that facilitated goal-setting, self-monitoring and supportive interaction between participants and their helper(s). Progression criteria were met, demonstrating that the intervention and trial methods were feasible and acceptable. A total of 109 participants (intervention, n = 73; control, n = 36) were recruited, with 84 participants (77%: intervention, 71%; control, 89%) followed up at 12 months. Data were successfully collected for most outcome measures (≥ 82% completion). Participants and helpers were generally positive, although helper engagement with the app was low. Of the 54 (74%) participants who downloaded the app, 48 (89%) used it twice or more, 28 helpers enrolled via the app, and 19 (36%) participants interacted with their helper(s) via the app. Interview data indicated that HelpMeDoIt! prompted support from helpers that often occurred without the helpers using the app. Limitations: Early technical problems meant that some participants and helpers had difficulty accessing the app. Ethical constraints meant that we were unable to contact helpers directly for interview. Conclusions: The HelpMeDoIt! study demonstrated that a weight loss intervention delivered via an app and a website is feasible and acceptable. Progression criteria were met, supporting further evaluation of the intervention. Future work: To further explore (1) the motivation and engagement of helpers, (2) the programme theory and (3) the effectiveness and cost-effectiveness of the intervention. Trial registration: Current Controlled Trials ISRCTN85615983. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 8, No. 3. See the NIHR Journals Library website for further project information.